2018
DOI: 10.2174/1568009617666170315162525
|View full text |Cite
|
Sign up to set email alerts
|

HIF1A is Overexpressed in Medulloblastoma and its Inhibition Reduces Proliferation and Increases EPAS1 and ATG16L1 Methylation

Abstract: HIF1A knockdown in medulloblastoma cells lead to decreased cellular proliferation, suggesting that HIF1A can be a potential therapeutic target to be explored in the medulloblastoma. However, the mechanisms behind HIF1A protein stabilization and function are very complex and more data need to be generated to potentially use HIF1A as a therapeutical target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…C). Although some reports correlated it with tumor biology (Cruzeiro et al , ), few studies revealed its role in the invasion of GBM cells. On the contrary, many of the top downregulated TFs control cell cycle and stemness, such as MYT1 , SOX6 , and SOX4 , among which OLIG1 was the top one in shared TFs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C). Although some reports correlated it with tumor biology (Cruzeiro et al , ), few studies revealed its role in the invasion of GBM cells. On the contrary, many of the top downregulated TFs control cell cycle and stemness, such as MYT1 , SOX6 , and SOX4 , among which OLIG1 was the top one in shared TFs.…”
Section: Resultsmentioning
confidence: 99%
“…S8C). Although some reports correlated it with tumor biology (Cruzeiro et al, 2018), few studies revealed its role in the invasion of SRPX2 TFPI UBC BTBD19 LDHA CYSTM1 CHRNA9 ANKRD42 ALDOA TPI1 SPARCL1 LGALS3 TUBB6 STOM B4GALT1 PTGES TMEM54 FHL3 P4HA2 CXCL3 DHRS3 IL32 CLUL1 OPTN CASP1 HP SSPN ANG BIRC3 MAFB NUPR1 HSPB8 CA12 IL6 UST TNFAIP3 SELL SLC39A14 LOX TAGLN ENPP5 ADCK4 TBC1D10A AR ZNF132 TNFAIP2 C4orf47 CAV2 ANGPTL1 APLNR TMEM42 GPRC5A FBLN5 MYOF S1PR1 LRRC2 LOXL2 PALMD CTGF ZMYND12 NABP1 PRICKLE1 GALNT15 EIF1 CXCL10 SDC2 GRB10 DDIT4L SAA2 KIF22 MGP TUBB4A CNTN1 NAA16 VEZF1 STMN1 LPPR1 TNR MLLT11 SHD SCRG1 NSG2 MPPED2 BEX2 PTPRO MTAP SNAP25 NPPA KCND2 GNG4 LHFPL3 GPR17 MYT1 MAP2 KCNQ2 TAOK3 CKMT1B NINJ2 MTSS1L WSCD1 SNTG1 SLIT1 MICAL1 SOX4 TMEM132B OLIG1 APOD TCF12 AFAP1L2 ZDHHC22 RAB33A SNX22 ST20 RAPGEF4 TRIB2 ATCAY C14orf93 RTKN UBE2R2 PHLDA1 CAMSAP1 MMP16 FABP7 GRIA2 TSPAN7 TAGLN3 ETV1 GRID2 QSOX1 SMIM18 ZNF71 SETD9 CRISPLD2 LIMA1 ABHD14A PAFAH1B3 NRSN1 FGF14 HRASLS CD82 UCP2 GPM6A TRAK1 FXYD6 S100B HN1 IDH1 o at a a u ula gu gu at a a gu g l k k k k k k k k k n n n n on n ati ati at t t a at t at t t ul ua a a ation i i n o o on o on n n n n n i i f k k k k k k k k k k k k k k k k l l l la at a a a l ul u u ula a a ul ul ula a atio a a at a a a l l la a a a a a o of o o of of o o o o o g g g g k kinase activity a kin ki as na a ki k containi o on regulation of protein kinase activity p egu tio p p tio t lati n reg g eg eg tio io a a gu g g gul la la eg g g g g re r at at ti t t t at metabolic process metabolic process ab ab ab ab a a m m me me me me me e n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n io io o io io io o g g g eg eg g g g g n n n n n n n n n n n n n n n n n n n n re e re reg g g g g g g gu u u ula la ulation of tion of u u eg eg e e a a n o o on on g g g g g n o o o u u n io io g g g g regulat regulat g g g g eg eg g g regulation regulatio u u eg eg a g gu u u eg eg g eg ce cel el l el regu eg l ll ll l l l ll atio at on n egu g g g l l l l ty y ty y ty y l motilit mo l l mo m l ilit m tilit mo o o egulation of developmental process n of de ulatio tion of ula gula gu ation o ula ula ul g of de n of de e n n n n ev e e l a egu reg egu p p p od od od n n n n n n n n n on on n n n n n n n n a a a a m m n n n n n g pro rote e ro rote e ote ein o od olic olic metabo meta me regulation of cellular protein n of ce cellular regulation of ce of ce cellul ll l a e ell el e of f of of la l la l g g c c c c ce e e e e regulation o regulation o regu regu re re regulation regulatio eg eg re r at at at a n n reg eg e e re re e e re ula ula ula la egu eg g g g g g g gu atio ati tio ti at a metabolic process me metabo metab aniz on on n n org org org niza niza rga n o n n on n organ g ga rg rg g rg ganiz z an niz iz n org r or r r r rg on differen ffe iffe n n n ffe ff ffe n d d fere n d...…”
Section: Identify Crucial Factors Involved In the Acquisition Of Invamentioning
confidence: 99%
“…Very little is known about the regulation of the HIF-2α gene, apart that it can be regulated by E2F1 [ 43 ], its promoter can be methylated [ 56 , 57 ], and that HDACs can repress both HIF-2α and HIF-1α genes [ 44 ]. We could also confirm that indeed depleting HDAC1 or treating cells with the class I and II HDAC inhibitor TSA resulted in increased levels of HIF-1α and HIF-2α, observed at mRNA ( Figure 3A and B ) and protein level ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…The influence of hypoxia on the TME of paediatric cancers is documented in multiple studies. [68][69][70][71] Hypoxia features in the microenvironment of bone marrow, and increased HIF-1α expression and the acquisition of a glycolytic phenotype (through AKT/mammalian target of rapamycin [mTOR] signalling activation) was demonstrated in co-cultures of leukaemic cells with bone marrow-derived mesenchymal stem cells under hypoxic conditions. 68 Medulloblastoma cell lines upregulate HIFs under hypoxic conditions, and a decrease in cellular proliferation was observed in response to knockdown of the HIF1A gene.…”
Section: Hypoxia-targeted Treatment Strategy 1: Increasing Oxygen Avamentioning
confidence: 99%